The long noncoding RNA Blnc1 orchestrates homeostatic adipose tissue remodeling to preserve metabolic health - Xu-Yun Zhao; Siming Li; Jennifer L. DelProposto; Tongyu Liu; Lin Mi; Cara Porsche; Xiaoling Peng; Carey N. Lumeng; Jiandie D. Lin (Elsevier, 2018)
Objective: Long noncoding RNAs (lncRNAs) are emerging as powerful regulators of adipocyte differentiation and gene expression. However, their significance in adipose tissue metabolism and physiology has not been demonstrated in vivo. We previously identified Blnc1 as a conserved lncRNA regulator of brown and beige adipocyte differentiation. In this study, we investigated the physiological role of Blnc1 in thermogenesis, adipose remodeling and systemic metabolism. Methods: We generated fat-specific Blnc1 transgenic and conditional knockout mouse strains and investigated how adipocyte Blnc1 levels are causally linked to key aspects of metabolic health following diet-induced obesity. We performed studies using cultured adipocytes to establish cell-autonomous role of Blnc1 in regulating adipocyte gene programs. Results: Blnc1 is highly induced in both brown and white fats from obese mice. Fat-specific inactivation of Blnc1 impairs cold-induced thermogenesis and browning and exacerbates obesity-associated brown fat whitening, adipose tissue inflammation and fibrosis, leading to more severe insulin resistance and hepatic steatosis. On the contrary, transgenic expression of Blnc1 in adipose tissue elicits the opposite and beneficial metabolic effects, supporting a critical role of Blnc1 in driving adipose adaptation and homeostatic remodeling during obesity. Mechanistically, Blnc1 cell-autonomously attenuates proinflammatory cytokine signaling and promotes fuel storage in adipocytes through its protein partner Zbtb7b. Conclusions: This study illustrates a surprisingly pleiotropic and dominant role of lncRNA in driving adaptive adipose tissue remodeling and preserving metabolic health. Keywords: lncRNA, Adipose tissue remodeling, Brown fat, White fat, Whitening, Inflammation, Obesity